Analisis Pemanfaatan Jalur Pedestrian pada Kawasan CBD Kota Makassar - Rohana, Rohana; Pertiwi, Nurlita; Muzaki, Muzaki (Pascasarjana Universitas Negeri Makassar, 2020)
Many phenomena arise in the city, which boils down to the problem of pedestrian pathways that are ineffective and neglected to use them. The first: Knowing the factors that cause pedestrian paths do not use well, Secondly: Find the formulation of the model of application of environmental based walkability in accordance with the rules per city design. The location of the research is Jalan Sultan Hasanuddin to Jalan Pattimura and Jalan Slamet Riyadi which are integrated with the CBD (Central Business District) area with a research method combining qualitative and quantitative benefits. The research variables are physical comfort, spatial-visual comfort and non-physical comfort. The analysis was conducted with descriptive, discussion analysis and simple regression based on the significance value of the trial (α) = 0.05. The results showed that physical comfort variable (X₁) simultaneously had a strong relationship to comfort level (Y), whereas spatial-visual comfort (X₂), and non-physical comfort (X₃) had a weak relationship to comfort level. One of the factors that influence the comfort of the pedestrian path in the area of Sultan Hasanuddin Street - Pattimura Street - Slamet Riyadi Street is the aspect of physical comfort. For the formulation of a Walkability-based environmental concept, in general, namely The provision of pedestrian paths must connect, The need for coordination with related parties regarding the provision of pedestrian paths, Coordination of each party regarding the provision of supporting facilities.